Factors Influencing Production and Market Participation among Smallholder Tomato Growers in Makhuduthamaga Municipality, Greater Sekhukhune District of Limpopo Province, South Africa - Puseletso Perpetua Kalauba; Abenet Belete; Mmapatla Precious Senyolo (Wieś i Rolnictwo)
Agriculture plays a significant role in the economic sector in Limpopo province in terms of its contribution to the economy, and the number of employment opportunities it produces within local communities. The majority of people involved in agricultural practices are emerging farmers and smallholder/small scale farmers. The aim of the study was to determine and profile factors influencing production and market participation among smallholder tomato growers in Madibong and Manganeng Villages, Makhuduthamaga Municipality in Greater Sekhukhune District, South Africa. A purposive sampling technique integrated with a random sampling technique were used to collect primary data from 100 smallholder tomato farmers using structured questionnaires. The Multiple Linear Regression and the Logistic Regression models were used to analyse the socio-economic factors that influence tomato production and market participation among smallholder tomato farmers in the study area. The results of the study revealed that extension access, fertiliser application, marital status, income from production and use of agricultural equipment positively influence tomato production. While, the educational level, gender of the farmer, farming experience, marital status and farm size positively influence market participation, market distance negatively influences market participation among smallholder tomato farmers. Based on the findings of the study, it is recommended that there should be a comprehensive producer support programme that focuses primarily on subsidising smallholder farmers when purchasing production inputs.